Management of pneumatocele in an extremely low birth weight neonate with percutaneous pigtail catheter by ultrasound guidance - Sophia Hameedi; Helen Hu; Chantal Angueyra; Sandra Kabagambe; Vincent Duron; Elvira Parravicini (Elsevier, 2022)
Pneumatoceles are rare in neonates and most resolve spontaneously. However, pneumatoceles can persist and compromise cardiopulmonary function secondary to mass effect. Intervention aimed at decompressing the air cyst helps alleviate cardiopulmonary compression. We present the case of a 23 6/7 week gestation female infant born in the setting of severe maternal preeclampsia who developed respiratory failure associated with a pneumatocele that was successfully treated at the bedside with ultrasound-guided placement of a pigtail catheter. This novel intervention resulted in immediate decompression of the pneumatocele without recurrence which allowed stabilization of the patient for closure of a large patent ductus arteriosus (PDA) with subsequent improvement of her cardiopulmonary function and discharge home. Prior reports have shown successful percutaneous decompression using fluoroscopic guidance, in this report we show an ultrasound guided technique. This approach mitigates the distress associated with fluoroscopic-guided and operative interventions in these patients with compromised cardiopulmonary function. In addition, it eliminates the need for transportation in this fragile patient population.